The impact of e-Musrenbang implementation on development planning process in Banda Aceh City, Indonesia - Putra Rizkiya; Zainuddin Zainuddin; Abdi Dzil Ikram (Geuthèë Institute, Aceh, 2023)
Sustainable development requires a well established development planning process. In Indonesia, the community participates in the development planning process through the Development Planning Forum (Musrenbang). The conventional Musrenbang faces many obstacles. Hence, smart city innovation by using the E-Musrenbang application was applied. Banda Aceh City is one of the cities using E-Musrenbang. However, the effectiveness E-Musrenbang in the development planning process in Banda Aceh City has never been measured. This study aims to study the conditions and processes of development planning before and after using E-Musrenbang and assess its effectiveness in the development planning forum process in Banda Aceh City. Data were collected through questionnaires and supplemented with interviews. The analysis was conducted in a descriptive qualitative supported by quantitative methods. The results showed that using the E-Musrenbang application increased the development planning process's effectiveness in Banda Aceh City. Increased effectiveness was indicated by the better effectiveness in time and result elements. Meanwhile, the quality of work elements was also improved. In addition, public satisfaction with Musrenbang has also risen because E-Musrenbang increased transparency, accountability and community participation in the Musrenbang process. The implementation of E-Musrenbang also has a positive impact on planning effectiveness because development planning becomes more effective.